KORELASI USIA DAN JENIS KELAMIN TERHADAP KEJADIAN STROKE - Rondonuwu, Rolly Harvie Stevan; Dharmawan, Rio L; Prasetyo, Agus; Abidin, M. Zainal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stroke is a non-communicable disease that is the second leading cause of death in the world after heart disease. Based on data searches, it is known that there are cases of stroke at PON Hospital based on age and gender classification in 2021, namely ischemic stroke cases as many as 3882 cases while hemorrhagic stroke cases were 803 cases consisting of male gender as many as 3001 patients and female 1684 patients and with an age range of under 15 years to over 65 years. The purpose of the study was to determine the correlation of age and gender to the incidence of stroke. The research design is a cross sectional retrospective study, namely data obtained by looking at patient medical record documents for the past 1 year. The research was conducted at the National Brain Center Hospital. The research was conducted in September 2023. The study population was all stroke patients who came to the Emergency Room of the National Brain Center Hospital. Sampe amounted to 72 respondents. The sampling technique used simple random sampling. Data analysis was performed univariate and bivariate. The results showed there was a relationship between age p value: 0.020 and gender p value: 0.000 to the incidence of stroke. It is recommended to prevent stroke by maximizing promotional or educational efforts to the public regarding the importance of stroke prevention through controlling hypertension, diabetes mellitus, heart disease and healthy living behaviors early on. These efforts can be done by utilizing social media through interesting content. Optimizing early detection of cardiovascular disease.Keywords: Gender, Age, Stroke